Arabidopsis K+ transporter HAK5-mediated high-affinity root K+ uptake is regulated by protein kinases CIPK1 and CIPK9 - Lara, Alberto; Ródenas, Reyes; Andrés González, Zaida; Martínez, Vicente; Quintero, Francisco J.; Nieves-Cordones, Manuel; Botella, M. Angeles; Rubio, Francisco (The journal of experimental botany, 2020)
Arabidopsis protein kinases CIPK1 and CIPK9, in addition to CIPK23, regulate K+ transporter HAK5-mediated K+ uptake, and their genes were induced by K+ deprivat
Gesehen am 21.10.2020